Olika mönster mellan genetisk variation och lokal anpassning hos tall - 746 obesläktade genotyper från 24 olika populationer av tall från Norra Europa - Hall, David (Swedish National Data Service, 2021)
In this study, we sampled 54 Scots pine populations from the Norwegian coast over the Arctic Circle to western Russia covering 47.3 longitudes or more than 1/8th of the earth’s circumference, which represents the most comprehensive coverage of Northern Europe to date. We inferred variation in autumn phenology and dormancy progression from freeze hardiness tests conducted on >5000 seedlings, of which >900 seedlings from 24 populations were genotyped using genotyping-by-sequencing (GBS). Our main goal was to evaluate adaptive responses in Scots pine at phenotype and genotype levels. Evaluation of cold hardiness along environmental and geographical gradients would contribute to an understanding of the performance of these gradients for predicting freeze damage levels. The genotype data allow evaluation of genetic variance across landscapes and thus shed light on the degree of genetic-environmental association and the recolonization history of Scots pine in Scandinavia. Text file as gzipped vcf (.vcf.gz). See "pheno_pop.txt" for more information on each individual. I den här studien undersökte vi den lokala anpassningen av tidspunkten för invintring och den genetiska variationen hos naturligt tallbestånd i norra Europa. Det geografiska området av studien sträcker sig från Norge i väster till och Komi-regionen i västra Ryssland fram till Uralbergen. Drygt 5000 frön från 56 populationer såddes upp och utsattes för frystemperaturer för att skatta deras frosttolerans och variationen i egenskapen över det geografiska området av denna studie. Från 24 av dessa 56 populationer samlades barr för att extrahera DNA till genotypning för att också kvantifiera den genetiska variationen hos tall i norra Europa och för att undersöka om det finns en tydlig populationsstruktur. Dessutom skulle det studeras om det finns spår av lokal anpassning i den del av genomet som sekvenserades och om dessa spår går att koppla till variationen i frosttolerans. Text fil enligt vcf format som är komprimerad med GNU zip (.vcf.gz). Se ...